2022
DOI: 10.3389/fendo.2022.1026262
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating health outcomes in the treatment of hypothyroidism

Abstract: Clinical hypothyroidism is defined by the inadequate production of thyroid hormone from the thyroid gland to maintain normal organ system functions. For nearly all patients with clinical hypothyroidism, lifelong treatment with thyroid hormone replacement is required. The primary goal of treatment is to provide the appropriate daily dose of thyroid hormone to restore normal thyroid function for each individual patient. In current clinical practice, normalization of thyrotropin (TSH) level is the primary measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…Syndrome T or SORSHOT, i.e., continued symptoms and reduced quality of life in treated www.nature.com/scientificreports/ hypothyroidism and AIT continues to be a challenge in about 10% of patients with thyroid diseases 2,9,26,44-46 . Multiple hypotheses have been proposed for an explanation of this common, yet poorly understood condition, but up to now no satisfactory solution is available [47][48][49][50][51] . Therefore, research programs addressing potential pathophysiological mechanisms of syndrome T are highly needed.…”
Section: Discussionmentioning
confidence: 99%
“…Syndrome T or SORSHOT, i.e., continued symptoms and reduced quality of life in treated www.nature.com/scientificreports/ hypothyroidism and AIT continues to be a challenge in about 10% of patients with thyroid diseases 2,9,26,44-46 . Multiple hypotheses have been proposed for an explanation of this common, yet poorly understood condition, but up to now no satisfactory solution is available [47][48][49][50][51] . Therefore, research programs addressing potential pathophysiological mechanisms of syndrome T are highly needed.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrate that thyroid hormone deficiency during hibernation is restricted to the CNS and does not extend to peripheral levels of T3 and T4. Hibernating squirrels thus present a remarkable animal model in which central thyroid hormone function is depressed while essential peripheral thyroid function on internal organs and general metabolic processes is preserved 49 , 50 . Central thyroid hormone has been implicated in the seasonal shifts in reproduction and food intake in non-hibernating animals, including Siberian hamsters, sheep, photoperiodic F344 rats 51 54 and hibernating arctic ground squirrels 55 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that squirrels exhibit T3 deficiency in the hypothalamus during IBA, and that restoration of T3 reverses anorexia, demonstrating that long-term suppression of hunger during hibernation is, at least partially, due to central hypothyroidism. Thyroid hormone deficiency is specific to the CNS and does not affect peripheral levels of T3 and T4, obviating the adverse effects of hypothyroidism on internal organs 35,36 and preserving the involvement of thyroid hormones in increasing thermogenic capacity prior to squirrels entering hibernation.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrate that thyroid hormone deficiency during hibernation is restricted to the CNS and does not extend to peripheral levels of T3 and T4. Hibernating squirrels thus present a remarkable animal model in which central thyroid hormone function is depressed while essential peripheral thyroid function on internal organs and general metabolic processes is preserved 49,50 . Central thyroid hormone has been implicated in the seasonal shifts in reproduction and food intake in non-hibernating animals, including Siberian hamsters, sheep, photoperiodic F344 rats [51][52][53][54] and hibernating arctic ground squirrels 55 .…”
Section: Discussionmentioning
confidence: 99%